A systematic review of dietary protein during caloric restriction in resistance trained lean athletes: A case for higher intakes - Helms, E. R.; Zinn, C.; Rowlands, D. S.; Brown, S. R. (International Journal of Sport Nutrition and Exercise Metabolism, 2014)
Caloric restriction occurs when athletes attempt to reduce body fat or make weight. There is evidence that protein needs increase when athletes restrict calories or have low body fat. Purpose: The aims of this review were to evaluate the effects of dietary protein on body composition in energy-restricted resistance-trained athletes and to provide protein recommendations for these athletes. Methods: Database searches were per- formed from earliest record to July 2013 using the terms protein, and intake, or diet, and weight, or train, or restrict, or energy, or strength, and athlete. Studies (N = 6) needed to use adult (= 18 yrs), energy-restricted, resistance-trained (> 6 months) humans of lower body fat (males = 23% and females = 35%) performing resistance training. Protein intake, fat free mass (FFM) and body fat had to be reported. Results: Body fat percentage decreased (0.5-6.6%) in all study groups (N = 13) and FFM decreased (0.3-2.7kg) in nine of 13. Six groups gained, did not lose, or lost nonsignificant amounts of FFM. Five out of these six groups were among the highest in body fat, lowest in caloric restriction, or underwent novel resistance training stimuli. However, the one group that was not high in body fat that underwent substantial caloric restriction, without novel training stimuli, consumed the highest protein intake out of all the groups in this review (2.5-2.6g/kg). Conclusions: Protein needs for energy-restricted resistance-trained athletes are likely 2.3-3.1g/kg of FFM scaled upwards with severity of caloric restriction and leanness.